The role of emotions in solving the frame problem: Emotions of the cognitive and/or perceptive type? - Silenzi, María Inés (Estudios de Filosofía, 2019)
Considering two of the main types of emotions, namely, perceptual emotions and cognitive emotions, in this paper we will examine which of them has a greater explanatory power for solving the frame problem. Additionally, we will analyze which of the main characteristics of perceptual and cognitive emotions type are appropriate when explaining how human beings determine relevance efficiently. We argue, assuming an intermediate position, that both types of emotions offer the necessary tools to explain how human beings solve the frame problem. This is due, on the one hand, to the experiential/corporal character of the perceptual emotions and, on the other hand, to the relationship that cognitive emotions establish with the achievement of goals when facing a determined situation.